2015
DOI: 10.1007/s00420-015-1086-2
|View full text |Cite
|
Sign up to set email alerts
|

A cytogenetic study of hospital workers occupationally exposed to radionuclides in Serbia: premature centromere division as novel biomarker of exposure?

Abstract: Identification of other phenomena related to radionuclide exposure, beside well known, may clarify recent problems in radiobiology concerning the biological response to low doses of ionizing radiation and its consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…Additionally, among the 32 MN studies, 23 evaluated the relationship (correlation or dose-response) between IR exposure and MN frequencies using two alternative indicators of exposure (using one or both indicators): cumulative dose from personal dosimeters (14 studies) and/or duration of exposure in years (16 studies). Among those, a significant association/correlation between cumulative dose or duration of exposure and MN frequencies were reported in 5/14 and 9/16 studies, respectively [ 23 , 32 , 38 , 61 , 64 , 65 , 74 , 77 , 82 ]. Additionally, in professionals working in a nuclear medicine department, both MN and SCE levels were significantly higher during their occupational exposure compared to levels immediately after vacation period [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, among the 32 MN studies, 23 evaluated the relationship (correlation or dose-response) between IR exposure and MN frequencies using two alternative indicators of exposure (using one or both indicators): cumulative dose from personal dosimeters (14 studies) and/or duration of exposure in years (16 studies). Among those, a significant association/correlation between cumulative dose or duration of exposure and MN frequencies were reported in 5/14 and 9/16 studies, respectively [ 23 , 32 , 38 , 61 , 64 , 65 , 74 , 77 , 82 ]. Additionally, in professionals working in a nuclear medicine department, both MN and SCE levels were significantly higher during their occupational exposure compared to levels immediately after vacation period [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the only two studies that focused on PCD reported significantly higher frequencies in IR-exposed workers compared to unexposed, regardless of a specific PCD readout used [ 49 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Micronuclei are acentric chromosomal fragments, or whole chromosomes, lost during cell division because due to DNA damage. Formation is dependent on the capacity for DNA repair and the accumulation of DNA damage (41,42) .…”
Section: Discussionmentioning
confidence: 99%